Legal Review of Termination of Unilateral Agreements in the View of Law and Human Rights in the Era of Industrial Revolution 4.0 - Safitri Saraswati; Noor Saptanti; Jadmiko Anom Husodo (Proceeding of the International Conference on Law and Human Rights, 2024)
Human rights are inherent in every human being who has the same rights, including unilateral termination of an agreement, then these human rights are disturbed and not protected. The research method uses normative legal research, namely the doctrinal method, namely inventorying positive law, finding legal principles and doctrines, synchronizing existing laws and regulations and conducting research by reviewing and examining various existing literature. With the Legislative Approach, Historical Approach, Comparative Approach, and Conceptual Approach. The results of the study indicate that unilateral termination of an agreement has the potential to be categorized as an unlawful act if the unilateral termination of the agreement is carried out without a valid reason, violates the principles of propriety and law, and causes losses to other parties. In addition, unilateral termination of an agreement if carried out without a valid reason violates human rights related to the right to legal certainty and human freedom without discrimination.